Unusual Evolutions of Dissipative-Soliton-Resonance Pulses in an All-Normal Dispersion Fiber Laser - Yufei Wang; Lei Li; Junqing Zhao; Shuai Wang; Chaojie Shu; Lei Su; Dingyuan Tang; Deyuan Shen; Luming Zhao (IEEE Photonics Journal)
We experimentally report the novel evolutions of dissipative-soliton-resonance (DSR) pulses with respect to the pump power in an all-normal-dispersion fiber laser based on a nonlinear optical loop mirror. By solely increasing the pump power, pulse breaking of the DSR pulses was observed apart from the typical pulse broadening at a fixed pulse peak power. Instead of arbitrarily broadening with the increase in the pump power or directly losing the mode-locking state, the process of pulse breaking was accompanied by the multipulse state and harmonic mode-locking pulses evolving from the original DSR pulse. In addition, to the best of our knowledge, a narrowing of the DSR pulse with the increase in the pump power was observed for the very first time. Further results show that these unusual evolutions of DSR pulses could be attributed to the changes in several laser parameters resulting from the increasing pump power under specific operating conditions.